Pengaruh Motivasi Kerja dan Produktivitas Kerja Terhadap Kinerja Karyawan Pada Masa Pandemi PT Bank Central Asia Tbk Kantor Cabang Serang - Agustinna, Rizka; Sandra, Mela (Pascasarjana Universitas Primagraha, 2024)
This research aims to determine the effect of work motivation and productivity on employee performance at PT Bank Central Asia Tbk Serang Branch. Both directly and simultaneously. The method used is quantitative. The sampling technique used a saturated side and the sample obtained in this study was 77 respondents. Data analysis uses validity tests, reliability tests, class assumption tests, and regression analysis. The results of the hypothesis research (X1) can be seen t count > t table value (3.654 > 1.993) with